Filsafat Eksistensialisme Kierkegaard Dan Implikasinya Terhadap Praktik Pendidikan Dalam Meningkatkan Spiritualitas Peserta Didik - Ega Nasrudin; Ahmad Faishal Ramadhan; Muhamad Parhan (Jurnal Kajian Ilmiah, 2024)
This article aims to explore how Kierkegaard's existentialist philosophy views and its implications for educational practices that occur in improving students' spirituality. A qualitative approach with a literature study design is used for sources with procedures for conducting studies, collecting sources, and analyzing. The results of the study indicate that existentialist philosophy directs human development at a stage that recognizes religion or religiosity. The educational implications that can be applied from this view are divided into implications for students, implications for teachers, and implications for policy managers. For students, education is a way to get to know and become themselves better. In this case, teachers need to provide freedom and encourage students to be themselves. The goals and processes of education in this case should not only be oriented towards memorization but also the process of finding identity by each student.